2010
DOI: 10.1111/j.1469-8137.2010.03571.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat perception and signalling in plants: a tortuous path to thermotolerance

Abstract: SummaryAn accurate assessment of the rising ambient temperature by plant cells is crucial for the timely activation of various molecular defences before the appearance of heat damage. Recent findings have allowed a better understanding of the early cellular events that take place at the beginning of mild temperature rise, to timely express heat-shock proteins (HSPs), which will, in turn, confer thermotolerance to the plant. Here, we discuss the key components of the heat signalling pathway and suggest a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(186 citation statements)
references
References 62 publications
5
174
0
Order By: Relevance
“…A similar scenario was recently found in tomato leaves in which over-expression of a CWIN gene did not affect leaf hexose content but increased the levels of Glc-6-P and Fru-6-P, leading to a delay in leaf senescence under drought (Albacete et al, 2015). Hsfs and Hsps play important roles in the heat response of plants through preventing the misfolding of protein and regulating the intracellular transport and degradation of proteins (Vierling, 1991;Saidi et al, 2011;Hahn et al, 2011). For example, cosuppression of HsfA1 in tomato led to extreme sensitivity of plants and fruits to elevated temperatures (Mishra et al, 2002).…”
Section: Elevated Cwin Activity Enhances Tomato Fruit Set Under Lmhsmentioning
confidence: 83%
See 1 more Smart Citation
“…A similar scenario was recently found in tomato leaves in which over-expression of a CWIN gene did not affect leaf hexose content but increased the levels of Glc-6-P and Fru-6-P, leading to a delay in leaf senescence under drought (Albacete et al, 2015). Hsfs and Hsps play important roles in the heat response of plants through preventing the misfolding of protein and regulating the intracellular transport and degradation of proteins (Vierling, 1991;Saidi et al, 2011;Hahn et al, 2011). For example, cosuppression of HsfA1 in tomato led to extreme sensitivity of plants and fruits to elevated temperatures (Mishra et al, 2002).…”
Section: Elevated Cwin Activity Enhances Tomato Fruit Set Under Lmhsmentioning
confidence: 83%
“…Heat stress transcription factors (Hsfs) and heat shock proteins (Hsps) are central in conferring heat tolerance (Saidi et al, 2011;Hahn et al, 2011). Previous studies in tomato have identified three Hsf genes (HsfA1, HsfA2, and HsfB1) and four Hsp genes (Hsp100, Hsp90, Hsp70, and HspII17.6) that play important roles in heat stress response (Mishra et al, 2002;ChanSchaminet et al, 2009;Giorno et al, 2010;Hahn et al, 2011;Li et al, 2012).…”
Section: Cwin-elevated Transgenic Tomato Exhibited a Sustained Or Incmentioning
confidence: 99%
“…As argued by researchers, the basic discovery could ultimately establish to have vital implications for world food security [11]. However, Saidi et al [12] were of the opinion that when temperature elevates, the heat signal is probably transduced by several pathways for coming together into the final activation of HSFs, the expression of HSPs and the onset of cellular thermotolerance.…”
Section: Heat Sensing By Plantsmentioning
confidence: 99%
“…Among these stress factors, high temperature is a major abiotic factor affects metabolism, growth, development, reproduction, yield, and even survival of plants including crop plants like maize (Zea mays L.) (Li & Gong 2011;Saidi et al 2011;Mittler et al 2012;Wu et al 2012;Grover et al 2013;PiterkovĂĄ et al 2013). In crop plants, maize not only is a new model plant, but also the third most important food grain crop after wheat and rice, and heat stress is the principal cause of maize failure worldwide, global warming accentuates this problem (Leipner & Stamp 2009;Strable & Scanlon 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In crop plants, maize not only is a new model plant, but also the third most important food grain crop after wheat and rice, and heat stress is the principal cause of maize failure worldwide, global warming accentuates this problem (Leipner & Stamp 2009;Strable & Scanlon 2009). Numerous studies have clearly illustrated high temperature stress commonly leads to oxidative stress as result of peroxidation of membrane lipids, degradation of proteins, inactivation of enzymes, DNA damage, etc., (Saidi et al 2011;Mittler et al 2012;Wu et al 2012;Grover et al 2013;PiterkovĂĄ et al 2013;Tari et al 2013). The degree of oxidative stress is determined by the level of reactive oxygen species (ROS) such as superoxide radical (O .…”
Section: Introductionmentioning
confidence: 99%